Флуктуация массы семени Cucurbita pepo var. giramontia Duch. в зависимости от генотипа и погодных условий года репродукции - Хлебников, В.Ф.; Смурова, Н.В. (Фактори експериментальної еволюції організмів, 2013)
Aims. It is known that seed signs in comparison with vegetative bodies change more poorly. However stability of these signs from factors of environment is relative and when placing plants in new conditions of the environment they can be more subject to changes. Methods. Researches conducted in the conditions of 2005–2006 and 2008–2011. For calculation of ecological plasticity used methods of Eberhart, Russel (1966) and Kilchevsky, Hotyleva (1985). Results. Studied forms of a squash on the mass of a seed significantly differed among themselves in each of years of researches. Exception are 2008 and 2009 in conditions which distinctions between forms are doubtful. It is established that the sample 19/84 poorly reacts to change of weather conditions. The most changeable are samples 166/5 and 98/5. Conclusions. Fluctuation of weight of a seed of Cucurbita pepo var. giramontia Duch. is defined by features of a genotype and depends on weather conditions of year of a reproduction.

Key words: seed, weigth, fluctuation, genotype, conditions of year.